Pemberdayaan Remaja Dhufa dalam Meningkatkan Kemandirian di Pesantren Teknologi Informasi dan Komunikasi (PeTIK) Depok - Yuwafi Prilia Ramadhani; Amin Tohari (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Adolescence is often faced with various challenges from the community, school, and family environment. Adolescents from underprivileged families are often overshadowed by economic limitations that hinder access to quality education and skills development. One way to address this is by empowering adolescents through non-formal education by honing skills to improve their quality when entering the world of work. This study aims to determine the implementation of empowerment of underprivileged adolescents in increasing independence at the Information and Communication Technology Islamic Boarding School (PeTIK) in Depok using qualitative methods and data collection techniques through interviews, observation, and documentation. Data are presented in the form of descriptions and written reports, as well as drawing conclusions. The results show that PeTIK significantly helps underprivileged adolescents to gain education and real-world experience in the world of work. This empowerment is an effort made so that adolescents have the ability to develop their academic and non-academic potential. In addition, PeTIK has succeeded in increasing adolescent independence such as emotional independence, social independence, intellectual independence, and economic independence.